2014
DOI: 10.1002/2013jd021314
|View full text |Cite
|
Sign up to set email alerts
|

Optical extinction of highly porous aerosol following atmospheric freeze drying

Abstract: Porous glassy particles are a potentially significant but unexplored component of atmospheric aerosol that can form by aerosol processing through the ice phase of high convective clouds. The optical properties of porous glassy aerosols formed from a freeze-dry cycle simulating freezing and sublimation of ice particles were measured using a cavity ring down aerosol spectrometer (CRD-AS) at 532 nm and 355 nm wavelength. The measured extinction efficiency was significantly reduced for porous organic and mixed org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(53 citation statements)
references
References 155 publications
3
50
0
Order By: Relevance
“…More generally, it is interesting to point out that, in a recent work aiming at quantifying the optical extinction of highly porous aerosols, the results coming from various theoretical approaches including the DDA method were found to largely underestimate those of the corresponding experimental measurements [58]. Although the reasons of this discrepancy were not fully elucidated, it has been suggested that the DDA method cannot account for the large porosity leading to a high number of boundary subvolumes.…”
Section: Structurementioning
confidence: 99%
See 1 more Smart Citation
“…More generally, it is interesting to point out that, in a recent work aiming at quantifying the optical extinction of highly porous aerosols, the results coming from various theoretical approaches including the DDA method were found to largely underestimate those of the corresponding experimental measurements [58]. Although the reasons of this discrepancy were not fully elucidated, it has been suggested that the DDA method cannot account for the large porosity leading to a high number of boundary subvolumes.…”
Section: Structurementioning
confidence: 99%
“…Indeed, PDI calculations, based on the exact positions of the atoms in the porous structure, would not depend on any assumptions on the porous subvolumes as in the DDA approach. However, because PDI calculations are time consuming, considering very large porous nanoparticles like those usually encountered in atmospheric aerosol [58] could be not straightforward.…”
Section: Structurementioning
confidence: 99%
“…Jeong and Nousiainen (2014) demonstrated, using transmission electron microscopy analysis, that the internal structures of individual Asian dust particles were formed by the patterned arrangement of nano-to-micron-sized mineral grains and pores. Highly porous aerosol particles, obtained from proxies for organic compounds, were investigated by Adler et al (2013Adler et al ( , 2014 with focused ion beam -scanning electron microscopy techniques and a cavity ring-down system. Most of the information on volcanic vesicular, i.e., porous ash, particles was obtained from samples collected at the ground level.…”
Section: Introductionmentioning
confidence: 99%
“…Examples for which the refractive index was retrieved along with a size distribution can be found in the works by Toledano et al (2012), Waquet et al (2014), and references therein. Effective medium approximations were used in inverse problems by Abo Riziq et al (2007) and Adler et al (2013Adler et al ( , 2014 where refractive indices of laboratory-generated aerosols were retrieved by comparing the measured size-resolved extinction efficiency with Mie theory calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Adler et al, 2014): so-called cloud processing. Thus, such a freezedrying cycle might increase their ice-nucleating abilities.…”
Section: Introductionmentioning
confidence: 99%